주도적 아이디어 이론을 바탕으로 한〈헤어질 결심〉서사와 인물 분석 - 이수진(Soo-Jin Lee); 정재형(Jae-Hyung Jung) (한국콘텐츠학회 논문지, 24(6), 2024)
본 연구는 영화에서 주도적 아이디어의 역할을 살펴보기 위해 <헤어질 결심>을 중심으로 주도적 아이디어를 중심으로 한 서사와 캐릭터 전개가 어떻게 구체적인 메시지를 전달할 수 있는지를 탐구한다. ‘자신의 틀에서 벗어날 때 진정한 사랑을 이룰 수 있다’라는 영화의 주도적 아이디어와 서사구조, 인물 구성의 상호작용을 분석하여, 의미 있는 이야기를 만들어가는 데 있어서 잘 정의된 주도적 아이디어가 갖는 의의를 보여준다. 연구 결과는 일관된 주도적 아이디어가 내러티브와 캐릭터를 형성할 뿐만 아니라 관객의 이해를 풍부하게 하여 스토리텔링의 기본 요소가 된다는 것을 연구한다. This study examines the role of leading ideas in film, focusing on <Decision To Leave> to explore how narrative direction and character development centered around a leading idea can convey specific messages. Analyzing the interaction between the film's leading idea, "True love is achieved by breaking from convention," narrative structure, and character composition, it demonstrates the significance of a well-defined leading idea in creating meaningful stories. The findings suggest that a coherent leading idea not only shapes the narrative and characters but also enriches audience understanding, making it a fundamental element in storytelling. KCI Citation Count: 0